2021
DOI: 10.1002/ajb2.1771
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in patchy populations of a candidate foundation plant: a case study ofLeymus chinensisusing genetic and clonal diversity

Abstract: Premise The distribution of genetic diversity on the landscape has critical ecological and evolutionary implications. This may be especially the case on a local scale for foundation plant species because they create and define ecological communities, contributing disproportionately to ecosystem function. Methods We examined the distribution of genetic diversity and clones, which we defined first as unique multilocus genotypes (MLG), and then by grouping similar MLGs into multilocus lineages. We used 186 marker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 108 publications
(190 reference statements)
0
3
0
Order By: Relevance
“…Pol et al [ 33 ] suggested that perenniality could enable perennial grasses to make large reproductive investments despite harsh environmental conditions. However, little is known about the year-to-year variation in seed yield of L. chinensis growing in a finite space within the same habitat [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pol et al [ 33 ] suggested that perenniality could enable perennial grasses to make large reproductive investments despite harsh environmental conditions. However, little is known about the year-to-year variation in seed yield of L. chinensis growing in a finite space within the same habitat [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…L. chinensis has high nutritional value and good palatability; therefore, different types of L. chinensis meadows are excellent mowing and grazing grounds ( Jia, 1987 ; Zhu, 2004 ). Because of its economic and ecological significance, L. chinensis has received considerable attention ( Guo et al., 2021 ; Meng et al., 2022 ; Sun et al., 2022b ). However, its main companion species, such as L. secalinus , C. ripidula , C. pseudophragmites and C. epigeios , have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these species disproportionately contribute to maintaining habitat integrity and ecosystem resilience (Bertness and Callaway, 1994;Keith et al, 2017;Ellison, 2019;Bertness, 2020;Qiao et al, 2021). Understanding how these species cope with challenges from anthropogenic impacts is key to preserving the ecosystems they create and define (Gedan et al, 2009(Gedan et al, , 2011Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%